The Importance of Humanistic Approach in Human Resource Management Education - Asdlori Asdlori (Indo-MathEdu Intellectuals Journal, 2023)
Human resource management (HRM) education is one of the key aspects in the development of successful organisations and enterprises. HRM involves planning, developing, directing, and managing human resources so that they can contribute effectively to the achievement of organisational goals. The purpose of this study is to examine the importance of humanistic approach in HRM education. This research is a literature review that uses a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The results of the study show that the humanistic approach in human resource management (HRM) education has a very important and significant role in creating an empowered, inclusive, and productive work environment. This approach recognises human values, individual uniqueness, and the importance of mental well-being in an organisational context